Notes on Health as Balance, Harmony and Equilibrium - Lee, Zosimo E. (Philippine Social Sciences Review; Social Sciences and Health Issue, Ed. Carmen C. Jimenez, 2010)
This paper looks at the concept of health as the interaction between the body and the mind from the perspective of the concepts of balance, harmony and equilibrium. The notion of disease is a key to understanding ill-health.